Particle identification for Z = 25 – 28 exotic nuclei from seastar experimental data - B. D., Linh; N. D., Ton; L. X., Chung; A., Corsi; A., Gillibert; N. T., Khai; A., Obertelli; C., Santamaria; N., Paul (Nuclear Science and Technology, 2017)
The particle identification (PID) method based on TOF-Bρ-ΔE measurement at RIKEN are discussed, and its application for Z = 25 – 28 neutron-rich nuclei from SEASTAR (Shell Evolution And Search for Two-plus energy At RIBF) experimental data are presented. The results including the PID for beam and residual nucleus at BigRIPS and ZeroDegree, respectively, demonstrate that the reactions of interest are well separated. This ensures the precision in the data analysis later on.